2018
DOI: 10.1029/2018gl079901
|View full text |Cite
|
Sign up to set email alerts
|

Plant Physiological Responses to Rising CO2 Modify Simulated Daily Runoff Intensity With Implications for Global‐Scale Flood Risk Assessment

Abstract: Climate change is expected to increase the frequency of flooding events and, thus, the risks of flood‐related mortality and infrastructure damage. Global‐scale assessments of future flooding from Earth system models based only on precipitation changes neglect important processes that occur within the land surface, particularly plant physiological responses to rising CO2. Higher CO2 can reduce stomatal conductance and transpiration, which may lead to increased soil moisture and runoff in some regions, promoting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 41 publications
4
28
0
Order By: Relevance
“…One exception is a recent study by Kooperman et al (2018) who found that plant-physiological responses to a quadrupled CO 2 concentration are of similar importance for daily runoff extremes in the CESM ESM as radiative-induced precipitation changes. One exception is a recent study by Kooperman et al (2018) who found that plant-physiological responses to a quadrupled CO 2 concentration are of similar importance for daily runoff extremes in the CESM ESM as radiative-induced precipitation changes.…”
Section: 1029/2018ef001123mentioning
confidence: 99%
See 1 more Smart Citation
“…One exception is a recent study by Kooperman et al (2018) who found that plant-physiological responses to a quadrupled CO 2 concentration are of similar importance for daily runoff extremes in the CESM ESM as radiative-induced precipitation changes. One exception is a recent study by Kooperman et al (2018) who found that plant-physiological responses to a quadrupled CO 2 concentration are of similar importance for daily runoff extremes in the CESM ESM as radiative-induced precipitation changes.…”
Section: 1029/2018ef001123mentioning
confidence: 99%
“…Several studies have investigated the drivers of changes in runoff, typically focusing on annual runoff. One exception is a recent study by Kooperman et al (2018) who found that plant-physiological responses to a quadrupled CO 2 concentration are of similar importance for daily runoff extremes in the CESM ESM as radiative-induced precipitation changes. Gedney et al (2006), using the MOSES land surface model, attributed the increase in global annual runoff observed over the twentieth century mainly to stomatal closure in response to increasing CO 2 .…”
Section: 1029/2018ef001123mentioning
confidence: 99%
“…286 More efficient water use by plants can further cause increasing runoff responses to rainfall, particularly for extremes. 13,287,288 Precipitation and streamflow are also affected directly by human activities, and water use can offset and even dominate responses to climate change regionally. 289 Deforestation can drive increased streamflow as demonstrated by simulations and observations over the Amazon and East Africa, [290][291][292] although this can be counterbalanced by decreases resulting from irrigation.…”
Section: Changes In Characteristics Of Precipitation and Hydrologymentioning
confidence: 99%
“…Unfortunately, no daily runoff output is available in the CMIP5 archive for the four ESMs used here. However a similar experiment with one model, CESM1-BGC, which followed the same protocol as the 1pctCO 2 experiments in CMIP5 40 (http://kooperman.uga.edu/grl2018/), does have daily runoff and precipitation. These CESM1-BGC simulations differ from CMIP5 by including extended periods of fixed preindustrial and 4×CO 2 conditions after the 1% per year ramp-up period, the first twenty-years of which are analysed here.…”
Section: Methodsmentioning
confidence: 99%